Efficiency enhancement of CIGS solar cell by WS2 as window layer through numerical modelling tool - Sobayel K.; Shahinuzzaman M.; Amin N.; Karim M.R.; Dar M.A.; Gul R.; Alghoul M.A.; Sopian K.; Hasan A.K.M.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Conversion efficiency; Copper compounds; Defects; Efficiency; Energy gap; Gallium compounds; Indium compounds; Interface states; Layered semiconductors; Numerical models; Photovoltaic effects; Solar power generation; Tungsten compounds; Conduction band offset; Density of defects; Efficiency enhancement; Gallium selenides; Interface defect state; Photovoltaic parameters; Potential windows; Temperature sensitive; Thin film solar cells; energy efficiency; fuel cell; gallium; numerical model; photovoltaic system; solar power